Przyswajanie złożoności językowej przez uczniów z deficytami języka i mowy w nauczaniu włączającym - Karpińska-Szaj, Katarzyna; Lewandowska, Agata (Neofilolog, 2021)
The article reports on an action research study which uses reformulation as its key instrument. The aim of the study was to identify the individual characteristics of acquisition of complex structures in Polish (native language) and English (foreign language) by children with speech and language deficits, learning in an inclusive environment at the upper primary level. The analysis of the gathered data focuses on Polish and English structures used by special needs students and mainstream students in their inclusive educational environment, and on the students’ ability to build/reconstruct a narrative structure – according to the unique qualities of the input text. The observed trends help to plan and organise the teaching process, which also includes the rehabilitation of speech and language in a foreign language lesson.